2001
DOI: 10.1577/1548-8454(2001)063<0277:eodclo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Cod Liver Oil on Growth and Fatty Acids of Juvenile Hybrid Tilapia

Abstract: An 8‐week growth trial was conducted to determine the effects of different levels of cod liver oil (CLO) on growth and tissue fatty acids of male hybrid tilapia (Nile tilapia Oreochromis niloticus × blue tilapia O. aureus). Eight isonitrogenous and isoenergetic diets containing various percentages of dodecanoic acid and CLO (5.0:0, 4.5:0.5, 4.0:1.0, 3.5:1.5, 3.0:2.0, 2.0:3.0, 1.0:4.0, 0:5.0) were fed to triplicate groups of tilapia with an initial body weight of 0.83 g (SD = ±0.03). The fish were kept at 26 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 25 publications
3
19
0
2
Order By: Relevance
“…2006). However, many other studies reported that substitution of FO with other lipid sources would decrease flesh n‐3 HUFA (Chou et al. 2001; Bell et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006). However, many other studies reported that substitution of FO with other lipid sources would decrease flesh n‐3 HUFA (Chou et al. 2001; Bell et al.…”
Section: Discussionmentioning
confidence: 99%
“…1983). There are two possible reasons accounting for this: (i) the higher n‐3 HUFA in the diets was highly susceptible to oxidation and might led to poor palatability or digestibility (Chou et al. 2001; Du et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid tilapia fed a CLO diet showed a slight depression in growth and feed efficiency ratio that might be associated with the higher n-3 PUFA concentrations found in CLO (Ng et al 2001). Chou et al (2001) reported no growth depression in hybrid tilapia fed semi-purified Experimental conditions: water changed three times weekly, temperature was maintained at 28-32°C by using heater, and ammonia concentration was maintained at less than 0.3 mg/l with pH of 8.00. The fish were fed to apparent satiation diets with graded levels of CLO for up to 5% and suggested that hybrid tilapia may also require n-3 FAs for maximum growth.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (1998) found that growth rates of hybrid tilapia fed soybean oil and fish oil were similar and both were better than that of fish fed lard or HUFA. In contrast, studies by Chou and Shiau (1999) and Chou et al (2001) demonstrated that hybrid tilapia, in addition to their requirement for n-6 FAs, required EPA and/or DHA. To evaluate the requirements of FAs, several different means of altering the LA/LNA ratios have been developed in human and animal models (Blank et al 2002).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation